Pediatric allergic fungal rhinosinusitis with extensive intracranial extension – Case report and literature review - Alenzi, Haifa Lafi (Int J Surg Case Rep, 2020)
INTRODUCTION: Over the last two decades, allergic fungal sinusitis (AFRS) has become increasingly common. It’s defined as a noninvasive, benign inflammatory fungal disease of the sinuses which develops in young adults and adolescents. Patients often complain of symptoms like nasal obstruction, congestion, purulent or clear rhinorrhea, anosmia, and headache. The cases are also presenting clinically with symptoms like epiphora and eye discharge as a result of nasolacrimal gland obstruction. In this article, we will review a unique case of AFRS, in an adolescent male. The case was diagnosed with intracranial extradural extension. CASE REPORT: A 15 years old male with AFRS was diagnosed and managed. The case was diagnosed to have allergic fungal sinusitis based on Bent and Khun diagnostic criteria, presented with intracranial extradural extension. DISCUSSION: In our case, there were no irreversible complications except a recurrent polyp. The case was mainly complaining of long-standing nasal discharge and on-off headache with no orbital complaint and no other neurological signs. This shows a presentation of the fungal sinusitis and the need for aggressive intervention for AFRS both medically and surgically for pediatric patients as well. CONCLUSION: To conclude, despite AFRS being categorized as a benign, non-invasive disease, its presentation can range from simple nasal obstruction to signs and symptoms of intraorbital and/or intracranial complications; with pediatric cases being very aggressive. Careful clinical evaluation, detailed histopathological examination, navigation assisted endoscopic sinus surgery followed by steroid treatment, and a lifelong follow up to manage the recurrence.